A biorefinery for conversion of citrus peel waste into essential oils, pectin, fertilizer and succinic acid via different fermentation strategies - Patsalou, Maria; Chrysargyris, Antonios; Tzortzakis, Nikos G.; Koutinas, Michalis (My University, 2020)
A process for the valorization of citrus peel waste (CPW) has been developed aiming to produce succinic acid and a series of added-value products through the biorefinery platform. CPW was subject to physicochemical and biological treatment to isolate essential oils (0.43%) and pectin (30.53%) as extractable products, pretreating the material for subsequent production of succinic acid that enabled application of remaining biorefinery residues (BR) as fertilizer substitute. Cellulose, hemicellulose and lignin contents of CPW accounted for 22.45%, 8.05% and 0.66% respectively, while acid hydrolysis reduced hemicellulose by 3.42% in BR. Moreover, essential oils extracted from CPW included 17 compounds, among which D-limonene reached 96.7%. The hydrolyzate generated was fermented for succinic acid production using Actinobacillus succinogenes. Different batch experiments demonstrated that the combined use of corn steep liquor (CSL) and vitamins in a lab-scale bioreactor resulted in product concentration and yield that reached 18.5 g L−1 and 0.62 g g−1 respectively. Although simultaneous saccharification and fermentation (SSF) could not enhance succinic acid production, a fed-batch fermentation strategy increased succinic acid concentration and yield generating 22.4 g L−1 and 0.73 g g−1 respectively, while the mass of the platform chemical formed was enhanced by 27% as compared to the batch process. BR was explored as fertilizer substitute aiming to close the loop in the management of CPW towards development of a zero-waste process demonstrating that although the material imposed stress on plant growth, the content of potassium, phosphorus and nitrogen in the mixture increased.
Keywords: A. succinogenes; Biorefinery; Citrus peel waste; Fertilizer; Succinic acid